Spectrophotometric Determination of Promethazine Hydrochloride Based on Inhibition of Hemoglobin - HONG CHEN, YA; SHOU TIAN, FENG; FANG LIU, HUI (Asian Journal of Chemistry, 2010)
A highly sensitive and simple catalytic spectrophotometric method for the determination of promethazine hydrochloride based on inhibitory effect of promethazine hydrochloride on the hemoglobin-catalyzed the reaction of H2O2 and acid chrome blue K (ACBK) was developed. The concentration of promethazine hydrochloride is linear with the percentage inhibition (I %) of system under the optimal experimental conditions. The calibration graph is linear in range 6.23 × 10-8 to 1.56 × 10-5 mol L-1 with the detection limit of 9.32 × 10-10 mol L-1. This method can be used for the determination of promethazine hydrochloride in tablets and injection solution of promethazine hydrochloride with satisfactory results.